A Longitudinal Examination of Interpersonal Violence Exposure, Concern for Loved Ones During a Disaster, and Web-Based Intervention Effects on Posttraumatic Stress Disorder Among Adolescent Victims of the Spring 2011 Tornadoes. Issue 9 (May 2021) - Gilmore, Amanda K.; Price, Matthew; Bountress, Kaitlin E.; Zuromski, Kelly L.; Ruggiero, Ken; Resnick, Heidi
Natural disasters are common and devastating, and can affect the mental health of adolescents. It is also common for adolescents to have histories of interpersonal violence (IPV). The current study was a secondary data analysis of a larger randomized clinical trial and examined the moderating effect of IPV history and concern for loved ones during a disaster on treatment condition effects on posttraumatic stress disorder (PTSD) symptoms over time among disaster-exposed adolescents. Participants ( n = 979) were recruited postdisaster to participate in a randomized clinical trial examining the efficacy of a web-based intervention, Bounce Back Now (BBN), on mental health symptoms at 4 and 12 months postintervention. It was found that adolescents with an IPV history and who had caregivers that were concerned for loved ones during a disaster had more PTSD symptoms at baseline than those without such histories. Furthermore, caregiver concern for loved ones during a disaster moderated the effect of BBN on PTSD symptoms over time. Specifically, the BBN condition was most effective for adolescents who had caregivers who were concerned for loved ones during the disaster in reductions of PTSD symptoms over time. The current study provides further evidence for the use of technology-based interventions for individuals as a means to address mental health symptoms after a traumatic event, especially among those with more severe traumatic experiences.